Mobile augmented reality app for children with autism spectrum disorder (asd) to learn vocabulary (marvoc): From the requirement gathering to its initial evaluation - Khowaja, Kamran; Al-Than, Dena; Osman Hassan, Asma; Shah, Asadullah; Salim, Siti Salwah (Springer, 2020)
The use of different technologies for the intervention of children with autism spectrum disorder (ASD) has increased over the year with the increase in the number of children diagnosed with ASD. In recent years, among the different technologies, the researchers have started to use the augmented reality (AR) to provide the intervention of different skills to children with ASD. The use of AR has many benefits, including ubiquity, minimally work with a camera, among others. Despite several benefits, AR has been underutilized for the vocabulary learning of children with ASD. This paper presents the initial version of the Mobile augmented reality app for children with autism spectrum disorder (ASD) to learn vocabulary (MARVoc). The purpose of developing MARVoc is to support teaching staff at the centers based in Doha, Qatar, to provide an interactive learning environment to children with ASD. The requirements of the MARVoc were gathered from two centers for ASD in Doha; two specific use cases were created from which one use case was finalized for the development of MARVoc. The initial version of the MARVoc was developed; the feedback was taken from the staff working at centers for ASD in Doha, and MARVoc was updated.